1993
DOI: 10.2105/ajph.83.3.356
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of rehabilitation in the home: a study of Swedish elderly.

Abstract: OBJECTIVES. To investigate whether care of elderly and disabled patients could be more cost-effective after a short-term hospital stay, we examined the impact of a primary home care intervention program on functional status, use and costs of care after 6 months. METHODS. When clinically ready for discharge from the hospital, chronically ill patients with dependence in one to five functions in personal activities of daily living were randomized to physician-led primary home care with a 24-hour service, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
17

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 22 publications
0
30
0
17
Order By: Relevance
“…We used supplementary unpublished data for two of the studies [27,[29][30][31][32] in the analysis. Details of the characteristics and quality of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used supplementary unpublished data for two of the studies [27,[29][30][31][32] in the analysis. Details of the characteristics and quality of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The support in the trials was provided for variable durations. In the majority, support had been withdrawn by 16 weeks post-discharge, but in two trials [29][30][31][32][33] the exact duration of support was not stated, and in one the support was tapered over a period of 9 months [36]. All were open to some degree to selection bias, either by virtue of their small size or because allocation concealment was inadequate or unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen trials reported on some aspect of physical functioning 58,69,[71][72][73][74][75][76][77][78][79][80]82,84,86,88,90,93,95,96,99,102 ( Table 59 ). Eleven of these studies used physical function scales (e.g.…”
Section: Physical Functionmentioning
confidence: 99%
“…23 To address this problem we undertook a structured literature review and identified systematic and Cochrane reviews of early supported discharge, discharge planning from hospital to home and care transition interventions. [3][4]9,18,[23][24][25][26][27] The key components of successful service models included (1) more intensive rehabilitation; (2) working more closely with the patient and his or her relatives; and (3) bridging interventions with a dedicated transition provider, either a nurse or a case manager, as the clinical leader, with an over-riding emphasis on having an advocate to facilitate co-ordination of care and outreach to patients following discharge from hospital.…”
Section: Chapter 2 Introductionmentioning
confidence: 99%